2019
DOI: 10.12740/pp/94382
|View full text |Cite
|
Sign up to set email alerts
|

General health, sense of coherence and coping styles in parents participating in Workshops for Parents of Hyperactive Children

Abstract: Cel pracyocena zmian w zakresie ogólnego stanu zdrowia, poczucia koherencji oraz stylów radzenia sobie ze stresem rodziców dzieci i młodzieży z ADHD, uczestniczących w 12-tygodniowych ‘Warsztatach dla rodziców dzieci nadpobudliwych’.Metodagrupę eksperymentalną stanowiło n=186 matek i n=139 ojców (rodzice n=199 dzieci), a grupę odniesienia n=23 matki i n=19 ojców (rodzice n=24 dzieci), uczestniczących w okresie 12-tygodni w 1-2 standardowych wizytach lekarskich (teratment as usual). Rodzice z obu grup zostali p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This fills a gap in existing literature, which usually considers this area as two separate lines of study. So far, research linking the psychology of emotions and family psychology in Poland is extremely rare, and it is usually focused on issues of stress [ 49 , 50 ] and depression [ 51 ]; it also typically employs methods for assessing general affect [ 52 ]. However, the international literature suggests that parental feelings are extremely specific, and their study requires a specific approach; this need may be met by the PFI, which appears to be an effective tool for assessing parental feelings in both its original and Polish versions.…”
Section: Discussionmentioning
confidence: 99%
“…This fills a gap in existing literature, which usually considers this area as two separate lines of study. So far, research linking the psychology of emotions and family psychology in Poland is extremely rare, and it is usually focused on issues of stress [ 49 , 50 ] and depression [ 51 ]; it also typically employs methods for assessing general affect [ 52 ]. However, the international literature suggests that parental feelings are extremely specific, and their study requires a specific approach; this need may be met by the PFI, which appears to be an effective tool for assessing parental feelings in both its original and Polish versions.…”
Section: Discussionmentioning
confidence: 99%
“…Parents of children with autism face unique and difficult stressors associated with their child's disorder, but their personal characteristics may influence how they relate to stressful life events and can help them cope with some of the harmful effects associated with external stress (Costa et al, 2017;Duarte, 2005;Jurma, 2008;Neff & Faso, 2015). Given that there are some negative consequences for mothers of autistic children (from anger, physical and mental exhaustion, increased stress to various pathologies, such as anxiety, depressive disorders, affective and adjustment disorders) (Clauser et al, 2021;Dabrowska & Pisula, 2010;Gray, 1992;Hățiș, 2021;Neff & Faso, 2015;Pisula, 2002;Yu et al, 2016), it is important to find which strategies reduce these consequences in order to increase the level of perceived psychological well-being of mothers, mothers who, in turn, will have positive effects on the development, behavior and adaptability of children with autism, because it has been found that interventions addressed to parents improve their mental state and general well-being, thus being essential for achieving optimal outcomes for their children with ASD (Cachia et al, 2016). The impact of the diagnosis of autism on family relationships is very great.…”
Section: Parents Of Children With Autismmentioning
confidence: 99%
“…When coping strategies are not adequate, these challenges can affect couple and family relationships, the physical and mental health of parents, with an increase in the incidence of depressive disorders, anxiety, stress, also having an influence on the parental role (Jurma, 2008). The literature identifies that mothers of children with autism present more psychological consequences, have a higher level of distress and lower psychological well-being, even developing various pathologies (depressive disorders, anxiety, stress), all these leading to difficulties in managing the relationship with the child and to serious consequences in terms of his symptoms (Clauser et al, 2021;Dabrowska & Pisula, 2010;Neff & Faso, 2015;Pisula, 2002). A clear determinant of mental health is mothers' inability to set limits on children's behavior, a predictive factor for depression being the aggression shown by some children towards the adults around them, as well as mothers' idea that the blame for the child's illness is external ( external locus of control), which leads to feelings of helplessness and loss of control and direct influence over the child's situation (Cappe et al, 2011;Falk, 2014, cited in Hățiș, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Participation in parenting workshops dedicated to a specific disorder of a child (e.g., ADHD) or improving competences in diagnosing depression symptoms may lead to an increasing sense of resourcefulness and reduce feelings of anxiety and insomnia. Indirectly, the professional and non-professional (mutual) support allow for reducing the severity of parental stress (Pisula, Bryńska, Wójtowicz, Srebrnicki & Wolańczyk, 2019). Participation in parenting workshops increases the parental influence on children's behaviour.…”
Section: Mental Health Of Children and Adolescentsmentioning
confidence: 99%